Neovascular AMD: Where do we go from here? - Barakat, Mark R; Dugel, Pravin U (Nepalese Journal of Ophthalmology, 2016)
In the age of anti-vascular endothelial growth factor (VEGF) therapy, we are fortunate as clinicians to have three great options in the treatment of neovascular age-related macular degeneration (AMD). Yet we still face a dilemma, in that we lack a truly sustainable treatment strategy. For various reasons, as a group we cannot maintain a monthly injection regimen for patients and are giving far less, approximately half of that, be it bevacizumab, ranibizumab, or aflibercept (Holekamp et al, 2014). Unfortunately, this comes at a cost: changing from monthly to as-needed injections has been associated with a decline in visual acuity almost back down to baseline (Singer et al, 2012; Silva et al, 2013).